1984
DOI: 10.1136/oem.41.2.267
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of acetylcholine challenge test: a prospective study.

Abstract: Cedex, and Lormines, 57703 Hayange, France ABSTRACr Eleven hundred and nine iron mine workers aged 35 to 55 with normal chest radiographs were submitted to a pulmonary examination consisting of a questionnaire, a clinical examination, and pulmonary function testing including an acetylcholine challenge test. A positive response (decrease of FEV, of more than 10%) was observed in 210 subjects (Ace+). The remaining 899 had a negative response (Ace-). Bronchitis, asthma, dyspnoea, and obstructive syndrome were mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
2

Year Published

1992
1992
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 3 publications
1
14
0
2
Order By: Relevance
“…We find, again, in this ten year follow-up study, a high rate of mortality due to lung cancer (SMR = 3.7), confirming the results discussed in our previous papers (23,27). Neither silica levels nor ionizing radiation levels, which were low in these mines (less than 2.1% and 0.07 working levels, respectively), can satisfactorily explain this excess.…”
Section: Discussionsupporting
confidence: 78%
“…We find, again, in this ten year follow-up study, a high rate of mortality due to lung cancer (SMR = 3.7), confirming the results discussed in our previous papers (23,27). Neither silica levels nor ionizing radiation levels, which were low in these mines (less than 2.1% and 0.07 working levels, respectively), can satisfactorily explain this excess.…”
Section: Discussionsupporting
confidence: 78%
“…Although there is some controversy on this in longitudin~ epidemiological studies [29,30], airway responsiven 's app9~s to be of prognostic significance in prospective clinic~) studies in children [31] as well as in adults [32]. If these fmdings can be confmned in other studies, the prognostic value might become one of the major indications of challenge tests in research and clinical practice.…”
Section: Indications In Clinical Diagnosismentioning
confidence: 99%
“…The results from the methacholine challenge test for spirometric data were examined using two types of index: 1) Percentage decline in FEV 1 as a qualitative measure of BHR, which is usually defined by a 20% decline in FEV 1 [18]; nevertheless, some authors have suggested that a lower level of change could indicate the presence of BHR [7,19,20]; in the present study, three threshold values were considered: 20, 15 and 10% fall in FEV 1 where ∆FEV 1 % was defined by the following relation: 2) Dose-response slopes were established for each parameter by dividing the previous forced oscillation indices by the cumulative dose of methacholine.…”
Section: Discussionmentioning
confidence: 99%
“…A decline in respiratory function has been observed among subjects with BHR, suggesting that the latter might be a predisposing factor of bronchopulmonary obstructive disease [5,6]. In a longitudinal study of iron mine workers, PHAM et al [7] observed that the incidence of chronic bronchitis was higher and the decrease in forced expiratory volume in one second/forced vital capacity ratio (FEV 1 /FVC) more marked among hyperreactive subjects. These studies suggest the importance of early detection of BHR in groups exposed to respiratory pollutants.…”
mentioning
confidence: 99%